Daily Associations Among Self-control, Heavy Episodic Drinking, and Relationship Functioning: An Examination of Actor and Partner Effects - Crane, Cory A. (2014)
An emerging literature suggests that temporary deficits in the ability to inhibit impulsive urges may be proximally associated with intimate partner aggression. The current study examined the experience of alcohol use and the depletion of self-control in the prediction of relationship functioning. Daily diary data collected from 118 heterosexual couples were analyzed using parallel multi-level Actor Partner Interdependence Models to assess the effects of heavy episodic drinking and depletion of self-control across partners on outcomes of participant-reported daily arguing with and anger toward an intimate partner. Heavy episodic drinking among actors predicted greater arguing but failed to interact with either actor or partner depletion. We also found that greater arguing was reported on days of high congruent actor and partner depletion. Both actor and partner depletion, as well as their interaction, predicted greater partner-specific anger. Greater partner-specific anger was generally reported on days of congruent actor and partner depletion, particularly on days of high partner depletion. The current results highlight the importance of independently assessing partner effects (i.e., depletion of self-control), which interact dynamically with disinhibiting actor effects, in the prediction of daily adverse relationship functioning. Results offer further support for the development of prospective individualized and couples-based interventions for partner conflict.